2003
DOI: 10.1104/pp.016386
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a GALACTINOL SYNTHASE Gene in Tomato Seeds Is Up-Regulated before Maturation Desiccation and Again after Imbibition whenever Radicle Protrusion Is Prevented

Abstract: .)Raffinose family oligosaccharides (RFOs) have been implicated in mitigating the effects of environmental stresses on plants. In seeds, proposed roles for RFOs include protecting cellular integrity during desiccation and/or imbibition, extending longevity in the dehydrated state, and providing substrates for energy generation during germination. A gene encoding galactinol synthase (GOLS), the first committed enzyme in the biosynthesis of RFOs, was cloned from tomato (Lycopersicon esculentum Mill. cv Moneymake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 65 publications
7
116
2
1
Order By: Relevance
“…GolS is a key enzyme in the production of raffinose-family oligosaccharides; it represents the galactynol from UDP-galactose and myoinositol, which serves as a precursor of galactosyl to form raffinose, stachyose and verbascose. Studies of A. thaliana have shown that the transcription factor DREB up-regulates expression of gols; accumulation of raffinose in plants is associated with tolerance of environmental stresses like cold and dehydration (Downie et al, 2003). However, in our study Gmgols gene expression was down-regulated in both genotypes.…”
Section: Gm18srrna Gmdreb1acontrasting
confidence: 50%
“…GolS is a key enzyme in the production of raffinose-family oligosaccharides; it represents the galactynol from UDP-galactose and myoinositol, which serves as a precursor of galactosyl to form raffinose, stachyose and verbascose. Studies of A. thaliana have shown that the transcription factor DREB up-regulates expression of gols; accumulation of raffinose in plants is associated with tolerance of environmental stresses like cold and dehydration (Downie et al, 2003). However, in our study Gmgols gene expression was down-regulated in both genotypes.…”
Section: Gm18srrna Gmdreb1acontrasting
confidence: 50%
“…The transcription level of MoGolS1 gene also increased at moderate level in the leaves treated with cold for 12 h or 1 day. These data supported the findings of Taji et al [2002], who reported strong induction of AtGolS3 transcription when Arabidopsis plants were treated with cold for 10−24 h at 4 o C. Similar result was also reported by Downie et al [2003] mentioning that tomato galactinol synthase (LeGolS1) gene induction in the leaves of seedlings was maximum when treated with cold (5 o C) for 12 h. The transcription level of MoGolS1 gene after 2 days of cold treatment was weak and irregular (Fig. 6A).…”
Section: Discussionsupporting
confidence: 82%
“…Their accumulation in plants is associated with stressful environmental conditions such as cold, heat, or dehydration [Santarius, 1973;Santarius and Milde, 1977;Hinesley et al, 1992;Ashworth et al, 1993;Wiemken and Ineichen, 1993;Bachmann et al, 1994;Taji et al, 2002] when they presumably assist sucrose in ameliorating plant stress [Zhao et al, 2004]. It is also proposed to play significant roles in protecting cellular integrity during desiccation or dehydration and provides substrates for energy generation during seed germination [Downie et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In knockout RS5 Arabidopsis mutants, the accumulation of raffinose was not observed during chilling stress (Zuther et al, 2004). In leaves of tomato (Solanum lycopersicum) and Arabidop-sis seedlings, the transcript levels of GolS and RS increased under environmental stress, such as cold and desiccation (Downie et al, 2003;Zuther et al, 2004). Arabidopsis contains seven genes that belong to the GolS family.…”
mentioning
confidence: 99%